A comparative study of physical and numerical modeling of tidal network ontogeny. Issue 4 (16th April 2014) - Zhou, Zeng; Olabarrieta, Maitane; Stefanon, Luana; D'Alpaos, Andrea; Carniello, Luca; Coco, Giovanni
<x xml:space="preserve">Abstract</x> We investigate the initiation and long‐term evolution of tidal networks by comparing controlled laboratory experiments and their associated scaling laws with outputs from a numerical model. We conducted numerical experiments at both the experimental laboratory scale (ELS) and natural estuary scale (NES) and compared these simulations with experimental data and field observations. Sensitivity tests show that initial bathymetry, frictional parametrization, sediment transport, and bed slope terms play an important role in determining the morphodynamic evolution and the final landscape. Consistent with experimental observations, the morphodynamic feedbacks between flow, sediment transport, and bathymetry gradually lead the system to a less dynamic state, finally reaching a stable network configuration. In both the ELS and NES simulations, the initially planar lagoon with large intertidal areas is subject to erosion, indicating ebb‐dominance. Based on quantitative analyses of the ELS and the NES simulations (e.g., geometric characteristics and relationship between modified tidal prism and cross‐sectional area), we conclude that numerical simulations are consistent with laboratory experiments and show that both type of models provide a realistic, albeit simplified, representation of natural systems. The combination of laboratory and numerical experiments also allowed us to explore the possibility of reaching a long‐term morphodynamic equilibrium. Both the physical and numerical models approach a dynamic equilibrium characterized by negligible gradients in sediment fluxes. The equilibrium configuration appears to be consistent with traditional relationships linking tidal prism and cross‐sectional area of the inlet. Finally, this contribution highlights the significance of complementary research between experimental and numerical modeling in investigating long‐term morphodynamics of tidal networks.